Impurity poisoning as a mechanism for the formation of zircon oscillatory growth zones - Marisa D. Acosta; James M. Watkins; Denis Fougerouse; Michelle L. Foley; Oliver Plümper; David W. Saxey; Steven M. Reddy; Mark H. Reed (Contributions to Mineralogy and Petrology, 2026)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Counterclockwise P-T-t path, cyclic crustal anatexis and magmatic tempo in accretionary orogens: A case study in the Devonian arc of Central Patagonia, Argentina - Emiliano M. Renda; Paulo Marcos; Sebastian Oriolo; Benita Putlitz; Lukas Baumgartner; Pablo González; Michelle L. Foley; Victor Ruiz González; Haroldo Vizán (Gondwana Research, 2025)

High-precision U Pb geochronology of an ignimbrite flare-up in a silicic large igneous province (Chon Aike, Patagonia) - Michelle L. Foley; Sean P. Gaynor; Benita Putlitz; Lukas P. Baumgartner (Lithos, 2024)

Integrated textural and geochemical analysis of igneous zircon by atom probe tomography - Michelle L. Foley; Elias M. Bloch; Stephan S.A. Gerstl; Benita Putlitz; Lukas P. Baumgartner (Contributions to Mineralogy and Petrology, 2024)
Mechanisms relating to growth and/or compositional modification of zircon occur at the atomic scale. For felsic igneous systems, processes responsible for growth patterns in zircon have previously remained elusive as the volume of material needed to analyze these compositional features using traditional in-situ methods is considerably larger than the typical sub-micron scale distribution of trace elements. To illuminate some of these driving forces, we characterize and quantify minor and trace element concentrations in igneous zircon grains by combining methods of cathodoluminescence (CL) imaging, electron microprobe microanalysis (EMPA) elemental maps for Hf, Y, Yb and U or Th, and atom probe tomography (APT). We focus on igneous zircon from the Chon Aike Silicic Large Igneous Province (Patagonia) that provide novel insights into (1) dissolution and re-crystallization during crustal anatexis, (2) crystallization to produce oscillatory zonation patterns that are typical of igneous zircons, and (3) the incorporation of trace element impurities (e.g., P, Be, and Al) at the nanoscale. Significantly, these APT volumes provide nanoscale sampling of boundaries between oscillatory growth zones in an igneous zircon to reveal compositional zoning of Y and, to a lesser extent P, which appear as high-angle, planar features. These concentration boundaries measured on the order of 10 to 12 nm are difficult to reconcile with proposed mechanisms for generating fine-scaled oscillations. Lastly, we fit diffusional profiles to measured Y concentrations to provide an estimate on the maximum timescales of zircon growth prior to eruption, as a function of the temperature at which diffusion occurred. When combined with known pressure-temperature-time paths for the magmatic system considered, these extremely short diffusion profiles that are resolvable by APT provide a powerful method to constrain timescales of crystal growth.

Identifying crustal contributions in the Patagonian Chon Aike Silicic Large Igneous Province - Michelle L. Foley; Benita Putlitz; Lukas P. Baumgartner; Emiliano M. Renda; Alexey Ulianov; Guillaume Siron; Massimo Chiaradia (Contributions to Mineralogy and Petrology, 2023)
The volcanic rocks of the Chon Aike Silicic Large Igneous Province (CASP) are recognized as magmas dominantly produced by crustal anatexis. Investigating the zircon of the CASP provides an opportunity to gain further insight into geochemical and isotopic differences of the potential magmatic sources (i.e., crust versus mantle), to identify crustal reservoirs that contributed to the felsic magmas during anatexis, and to quantify the contributions of the respective sources. We present a combined zircon oxygen and hafnium isotope and trace element dataset for 16 volcanic units of the two youngest volcanic phases in Patagonia, dated here with LA-ICP-MS U–Pb geochronology at ca. 148–153 Ma (El Quemado Complex, EQC) and ca. 159 Ma (western Chon Aike Formation, WCA). The EQC zircon have 18 O-enriched values (δ 18 O from 7 to 9.5‰) with correspondingly negative initial εHf values (− 2.0 to − 8.0). The WCA zircon have δ 18 O values between 6 and 7‰ and εHf values ranging between − 4.0 and + 1.5. Binary δ 18 O-εHf mixing models require an average of 70 and 60% melt derived from partial melting of isotopically distinct metasedimentary basements for the EQC and WCA, respectively. Zircon trace element compositions are consistent with anatexis of sedimentary protoliths derived from LIL-depleted upper continental crustal sources. The overlap between a high heat flux environment (i.e., widespread extension and lithospheric thinning) during supercontinental breakup and a fertile metasedimentary crust was key in producing voluminous felsic volcanism via anatexis following the injection and emplacement of basaltic magmas into the lower crust.